Pemahaman Siswa Tentang Equal Sign Dalam Menyelesaikantugas Matematika - Setiawan Budi Sartati; Su banji; Sis woro (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2019)
Equal sign is a sign that is used as a link in a sentence of equality. Equal sign translated into three sections, among others, as operational namely the equal sign to show results, the equal sign as basic relationalis expressed similarity operating results, and the equal sign as substitution of implying the replacement of one representation to another. Observations indicate that the students glued to view only the equal sign as operational, it is seen from a mistake appears to the statement continued, eg 3 + 4 = 7 + 2. In response, researchers conducted a study to describestudents understanding of the equal sign to solve mathematical tasks. This study was included in the qualitative descriptive study. In this study, the data collected is the data of students work and verbal data (the interview). The subjects were six students of 7th class of MTs Attariqie Malang 2014/2015 (Junior High School), with details of two high-ability students, two students capable of being, and two low-ability students. Students' understanding of the equal sign examined further by providing tests and interviews in six research subjects. Interviews were conducted individually after the students work on the problems individually. The mathematical task load arithmetic and algebra problems. Based on the results of the study, all subjects were able to understand the equal sign as operational and the equal sign as substitution. For equal sign as the basic relational, only high-ability students were able to understand it. Understanding of medium and low student capable entrenched in operational pattern that is equal sign as operational cause confusion to understand equal sign as the basicrelational, eg,14+11=25+8where students only pay attention to the results of operations that 14 plus 11 is 25 without notice relationo f addition of 8.Keywords: equal sign, operational, basic relational, substitution, mathematic, arithmetic, algebra.